Cation Substitution in Earth‐Abundant Kesterite Photovoltaic Materials. Issue 4 (29th January 2018) - Li, Jianjun; Wang, Dongxiao; Li, Xiuling; Zeng, Yu; Zhang, Yi
Abstract: As a promising candidate for low‐cost and environmentally friendly thin‐film photovoltaics, the emerging kesterite‐based Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells have experienced rapid advances over the past decade. However, the record efficiency of CZTSSe solar cells (12.6%) is still significantly lower than those of its predecessors Cu(In, Ga)Se2 (CIGS) and CdTe thin‐film solar cells. This record has remained for several years. The main obstacle for this stagnation is unanimously attributed to the large open‐circuit voltage ( V OC ) deficit. In addition to cation disordering and the associated band tailing, unpassivated interface defects and undesirable energy band alignment are two other culprits that account for the large V OC deficit in kesterite solar cells. To capture the great potential of kesterite solar cells as prospective earth‐abundant photovoltaic technology, current research focuses on cation substitution for CZTSSe‐based materials. The aim here is to examine recent efforts to overcome the V OC limit of kesterite solar cells by cation substitution and to further illuminate several emerging prospective strategies, including: i) suppressing the cation disordering by distant isoelectronic cation substitution, ii) optimizing the junction band alignment and constructing a graded bandgap in absorber, and iii) engineering the interface defects and enhancing the junction band bending. Abstract : Cation substitution is one of the most promising solutions to overcome the large open‐circuit voltage ( V OC ) deficit in kesterite solar cells. This deficit is attributed to cation disorder and associated band tailing, unpassivated interfaces, and undesirable energy band alignment. Recent efforts and strategies are considered to overcome the V OC limit of kesterite solar cells using various cation substitution methods.